EP253 Is the revised 2018 FIGO staging system for cervical cancer associated with increased discrimination in prognosis for women previously staged as IB disease? A retrospective, dual-institutional study. (1st November 2019) - Ayhan, A; Aslan, K; Bulut, AN; Akilli, H; Oz, M; Haberal, A; Meydanli, MM
Abstract : Introduction/Background: The purpose of this study was to validate the 2018 International Federation of Gynecology and Obstetrics (FIGO) staging system for cervical cancer. Methodology: Institutional cervical cancer databases of two high-volume gynecologic cancer centers in Ankara, Turkey were retrospectively analyzed. Only women with 2009 FIGO stage IB1 or IB2 disease that underwent radical hysterectomy with pelvic and para-aortic lymphadenectomy were included. Survival curves were generated using Kaplan-Meier plots, and the log-rank test was used for survival comparisons. The Cox proportional hazards regression model was used to obtain hazard ratios (HRs) and 95% confidence interval (CI). Results: Data from 425 women were analyzed. Stage migration was observed in 372 (87.5%) patients. According to the 2018 FIGO staging system, there was no significant difference in overall survival rates between stage IB1 (n=53) and IB2 (n=127) disease (95.2% vs. 89.3%, respectively; p=0.23) as well as between stage IB2 (n=127) and IB3 (n=95) disease (89.3% vs. 84.2%, respectively; p=0.12). Similarly, we were not able to demonstrate a significant difference in overall survival rates between stage IIIC1 (n=114) and IIIC2 (n=36) disease (79.0% vs. 67.2%, respectively; p=0.34). Conclusion: The revised FIGO staging system seemed to reflect OS adequately as there was a clear statistical tendency for poorer OS rates with increasing stage. However, its prognostic discrimination was not statistically significant. The 2018 FIGO staging system seems to suffer from increased number of sub-stages leading to limited number of patients in each sub-stage which results in diminished statistical power. Disclosure: Nothing to disclose.